Theater, culture, and community in Reformation Bern, 1523-1555 - Ehrstine, Glenn (Studies in medieval and Reformation thought, 2002)
This study examines the sociocultural context of ten plays, including 15 song texts, performed during the formative years of the Bernese Reformation. It treats not only three pre-reform carnival plays by Niklaus Manuel, but also six newly edited works by local court secretary Hans von Rute.